Seabirds and Coastal Waterbirds of Eastern Libya: From Ain Al-Ghazala to the Gulf of Bomba- Multi-Site Surveys and Hunting Pressure - Dr. Abdoul Baset Hassen Aboushiba (African Journal of Advanced Pure and Applied Sciences, 2025)
Eastern Libya’s coast from Ain Al-Ghazala to the Gulf of Bomba comprises a contiguous mosaic of lagoons, sabkhas, sandy beaches, rocky headlands, and inlets that support seasonally rich assemblages of seabirds and coastal waterbirds. This study delivers a standardized, multi-site assessment across that corridor to establish an updated species list, quantify spatial and seasonal patterns, and appraise hunting pressure. We implemented a stratified design with replicated vantage-point scans, shoreline line-transects, and sabkha circuits across three geographic clusters (west–central–east). Counts were aligned with international mid-winter and spring passage windows; detectability considerations were incorporated through effort normalization and distance bins on transects. Hunting pressure was evaluated using convergent field indicators (spent cartridges, hides, carcasses, nets/decoys, access tracks), weekly market checks, and semi-structured interviews, synthesized as a composite Hunting Pressure Index. We analyze richness, abundance, encounter rates, and diversity, and relate bird use to habitat type (lagoon, sabkha, beach, rocky headland, inlet) and to the pressure index using negative-binomial mixed models with site as a random effect. By integrating standardized bird counts with explicit human-pressure metrics, the work produces actionable baselines for enforcement routing, community outreach, and site-level management, while providing a replicable template for future monitoring. The approach also strengthens national alignment with international waterbird census practices and facilitates comparability with coastal segments elsewhere in Libya.